Building a Knowledge Graph on Video Transcript Text Data - Bagas Triaji; Widyastuti Andriyani; Bambang Purnomosidi DP; Faizal Makhrus (LPPM UTDI (d.h STMIK AKAKOM) Yogyakarta, 2022)
Youtube is a video platform which not only provides entertainment but also education in which knowledge can be dug based on video transcripts. The results of this knowledge can be formed as a knowledge graph to build a knowledge base that saves storage space. Moreover, it can be used for other purposes such as recommendation systems and search engines. Prosen built a knowledge graph using NLP to extract the text by identifying the subject-verb-object (SVO) and stored in the graph database. The construction of a knowledge graph on a Youtube video transcript was successfully carried out. However, there are still obstacles in the process of extracting text using NLP which is less optimal so it is possible that there is still a lot of knowledge that has failed to be obtained.